Assessing the Consumer Knowledge and Perception on Health Benefits of Fish Consumption – Evidence from the Tribal Populace of Wayanad: Fish Consumption and Health Perceptions: Insights from Wayanad’s Tribal Population - Gopika R.; Joshy C. G.; Sajeev M. V.; Akshay P.; Mohanty A. K.; Aparna Radhakrishnan; Suseela Mathew; Ravishankar C. N. (Fishery Technology, 2024)
This study evaluated the knowledge, perception, and receptiveness of tribal population in Wayanad, Kerala, towards the health benefits on the consumption of fish and fish-based products. Data on 200 households were collected through a questionnaire, where 78% of respondents were females and 22% were males. The results of the survey indicated that only 34.5% of the respondents exhibited satisfactory knowledge on health benefits of fish consumption with an average score of 2.97. About 68.5% of the respondents had an unsatisfactory perception towards the benefits of fish consumption with an average score of 20. Misconceptions regarding the nutritional value of fish were prevalent among the respondents, including beliefs that fish lacks essential vitamins (76%) and is not a good source of omega-3 fatty acids (93.5%). However, positive perceptions were observed, with 89.5% recognizing potential of fish in preventing heart attacks and strokes. Moreover, 81% acknowledged that the consumption of fish can reduce the shrinkage of brain during old age. A significant share showed willingness to try fish-based products like fish balls and fish pappad, but most of them were less receptive to take fish-based products due to unfamiliarity, pricing and availability issues. These findings highlight the importance of targeted public health initiatives to address misconceptions about the consumption of fish to promote the consumption of fish and fish-based products for their numerous health benefits through awareness programme and education. Implementing strategies to increase the availability and accessibility of innovative fish-based products could further enhance their adoption among consumers, which could improve overall health and nutritional security in the tribal community.